Book Review: Petrakis, Panagiotis E. Culture, Growth And Economic Policy. Berlin, Heidelberg: Springer-Verlag, 2014. 238 PP. - Setiawan, Andy Bangkit (Political Science Program, Universitas Negeri Semarang, 2016)
Lately, Indonesian exposed by a service called Go-Jek. Go-Jek is a multimedia based ojek (motorcycle taxi) which is launched in some cities in Indonesia, which the costumers can only use specific application provided by Go-Jek company to call the ojek riders who will take them to their destinations. Even amount of the cost charged can be shown by the costumers at the moment they order without any bargain with the riders like the conventional ojek. By all means, this facility cuts off all inefficiency, which felt by ojek costumers and riders. However, resistance arises from some particular people who work as conventional ojek riders. Even at some places violence done by conventional ojek riders to Go-Jek riders, does happen.